2000
DOI: 10.1111/j.1778-428x.2000.tb00034.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion Mortality and Morbidity in Orthopedic Surgery

Abstract: n the United States, more than 13 million red blood cell units are collected annually, and 11 million units are transfused to 3.4 million patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown no difference in patient function after total hip arthroplasty between groups with postoperative Hb levels of 9-10 g/dL and 10-12 g/dL. 3 It is possible to predict with some accuracy the need for transfusion after hip and knee arthroplasty. Bierbaum, in a study of nearly 10,000 patients, found a transfusion rate of approximately 50%.…”
Section: Peter Earnshaw Mbbs Frcs Frcs(c)mentioning
confidence: 99%
“…Studies have shown no difference in patient function after total hip arthroplasty between groups with postoperative Hb levels of 9-10 g/dL and 10-12 g/dL. 3 It is possible to predict with some accuracy the need for transfusion after hip and knee arthroplasty. Bierbaum, in a study of nearly 10,000 patients, found a transfusion rate of approximately 50%.…”
Section: Peter Earnshaw Mbbs Frcs Frcs(c)mentioning
confidence: 99%